1973
DOI: 10.1021/bi00741a009
|View full text |Cite
|
Sign up to set email alerts
|

Papain cleavage of rabbit secretory immunoglobulin A. Differential sensitivity of f and g subclasses

Abstract: Rabbit secretory immunoglobulin A (sIgA) was digested with papain in the absence of reducing agent and four fractions were isolated by gel filtration. Three of the four fractions, undigested sIgA, Fc~,, and Fabz, have previously been characterized (Hanly et ai. (1973), Biochemistry 12, 733); the fourth fraction (approximately 15% of the total protein) was identified as Fab,-like material by its sedimentation and antigenic properties. Each of the four fractions was analyzed for the allotypic specificities contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The Cag locus controls allotypic specificities on the constant region of alpha heavy chains (on both the Fc and Fd portions), and the VHa locus controls allotypic specificities on the variable region of the alpha chain (2,8,9). If no recombinant IgA molecules exist, rabbits heterozygous at the VHa and Cag loci would be expected to have only two types of IgA molecules (with respect to these two loci).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cag locus controls allotypic specificities on the constant region of alpha heavy chains (on both the Fc and Fd portions), and the VHa locus controls allotypic specificities on the variable region of the alpha chain (2,8,9). If no recombinant IgA molecules exist, rabbits heterozygous at the VHa and Cag loci would be expected to have only two types of IgA molecules (with respect to these two loci).…”
Section: Discussionmentioning
confidence: 99%
“…The g locus controls the allotypic specificities g74 and g75 on the constant part of alpha chains of a second subclass of IgA (8,9). The g74 and g75 allotypic specificities are each comprised of multiple antigenic determinants, some of which are present on the The phenomenon of allelic exclusion (11), in which only one of the two alleles at a given locus is expressed, exists for several immunoglobulin loci at the molecular and cellular levels (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Knight, Lichter, and Hanly (22) have reported detailed studies on secretory IgA of the rabbit, showing that molecules bearing the g genetic allotype are susceptible to papain cleavage, while those of the f allotype are highly resistant. Differences in susceptibility to proteases have also been found among human IgG subclasses (23).…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al (19), using a fluorescence-activated cell sorter, demonstrated that the precursor cells in Peyer's patches bear surface K-, but not it-chains. Subsequently, the tLminus, K-positive population, which contains the precursors of the IgA-producing plasma cells, was shown to contain a-positive cells detectable with antisera to IgA allotypes (20,21). However, the precursor cells have not directly been shown in transfer experiments to bear surface a-chains.…”
Section: Effect Of Anti-a-chain Antiserum On Homing Of Cellsmentioning
confidence: 99%